Role of Pcsk9 In The Diagnosis Thyroid Disorder in Patient Women - Mohammed, Hassanein Fadel; Jaber, Sarah Hassan (Medical Science Journal for Advance Research, 2021)
This study for the diagnosis of thyroid using pcsk9.The current study was conducted on seventy women patients suffering from thyroid disease attending in Center for diabetes and Endocrinology Unit in each of Al-Sadder Teaching Hospital and AL FURAT AL AWSAT Hospital in Al-Najaf province/ Iraq, and during the period from September until December 2017. The sample patients were divided into four study groups: premenopausal hypothyroidism patients group (20), postmenopausal hypothyroidism (15), premenopausal hyperthyroidism patients groups (17), and postmenopausal hyperthyroidism (18). The control group composed of 18 healthy women, also divided into premenopausal control and postmenopausal control. The results indicated a significant increase (p<0.05) in pcsk9 in hypothyroidism patients compared with the control group, while a significant decrease (p<0.05) in pcsk9 in hyperthyroidism patients compared with the control group. The results indicated a significant decrease (p<0.05) in pcsk9 in premenopausal hyperthyroidism patients compared with the control group, and a significant decrease (p<0.05) in pcsk9 in postmenopausal hyperthyroidism patients compared with the control group. The results indicated a significant increase (p<0.05) in pcsk9 in premenopausal hypothyroidism patients compared with the control group, and a significant increase (p<0.05) in pcsk9 in the postmenopausal hypothyroidism patients compared with the control group, also a significant increase in pcsk9 in postmenopausal than premenopausal.